Leadership styles, organizational behavior, and their impact on rational administrative decision-making: A systematic literature review and theoretical model in the Algerian context - Foudil, Azzoug; Zohra, Slimi Fatma (The International tax journal, 2026)
This paper aims to provide a theoretical analysis of the relationship between leadership styles and organizational behavior and their impact on rational administrative decision-making through a systematic review of contemporary literature and a critical review of previous Algerian studies. The paper adopts a critical analytical approach in examining major theories, such as transformational and transactional leadership theory (Bass & Avolio, 1994), social exchange theory (Blau, 1964), and bounded rationality theory (Simon, 1997). The review concluded that there is a theoretical consensus that democratic and transformational leadership styles are positively associated with rational decision-making, while the autocratic style is negatively associated with it. Furthermore, the literature showed that organizational behavior plays a mediating role in this relationship. The critical review of Algerian studies revealed clear knowledge gaps, including the examination of variables in isolation, the absence of mediation tests, and the neglect of the concept of rational decision-making. In light of the specificities of the Algerian environment (bureaucratic legacy and rigid hierarchical structures), the potential implications of these theoretical findings were discussed. Accordingly, the paper presents an integrated theoretical model to guide researchers and practitioners in Algerian public institutions.